PERAN DINAS PERHUBUNGAN BIDANG PERHUBUNGAN DARAT DALAM PENYELENGGARAAN DAN PERENCANAAN PELABUHAN PENYEBERANGAN RO-RO DI KABUPATEN BENGKALIS TAHUN 2015 - Perdana, Risky; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Ro-ro ferry ports in Bengkalis is a port that has prospects for development and the considerable potential in terms of geographical aspect and the opportunity to support the growth of the industry and the region's economy. The problems of this research are the Role of Department of Transportation Sector Land Transport Implementation and Planning in Ro-ro port in Bengkalis and the Patterns Transportation Agency Relationships with Private Sector Land Transport Implementation and Planning in Ro-ro port in Bengkalis. This research aims to knows the role of the Department of Transportation Sector Land Transport and the Pattern of Private Relationship with Implementation and Planning in Ro-ro port in Bengkalis.The method’s of this research is a qualitative method with the type of data used primary data and secondary data, data sources and documents obtained through informants research place. Data were collected by interview, observation and documentation, and then analyzed in a descriptive way to provide an overview of the research results.The results of this research are the role of the Department of Transportation Division of Land Transport in the administration and planning of ro-ro port in Bengkalis has not been able to provide optimum services because facilities such as docks and parking lots yet to be finalized, so that problems such as congestion, reliability of schedules and comfort aspects is still perceived by the user / passenger ship.Keywords: Strategy, Implementation, Planning